2019
DOI: 10.1101/538769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SynQuant: An Automatic Tool to Quantify Synapses from Microscopy Images

Abstract: Motivation:Synapses are essential to neural signal transmission. Therefore, quantification of synapses and related neurites from images is vital to gain insights into the underlying pathways of brain functionality and diseases. Despite the wide availability of synaptic punctum imaging data, several issues are impeding satisfactory quantification of these structures by current tools. First, the antibodies used for labeling synapses are not perfectly specific to synapses. These antibodies may exist in neurites o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…To gain further insight into the effect of taurine on synaptic machinery, we next focused on analyzing neurites (cropped 50 μm × 20 μm section of neurites extending from pyramidal neurons; see “Materials and Methods” section for detailed description) using the SynQuant plugin in ImageJ (Wang et al, 2020 ). This method allows for the identification of puncta and the detailed quantification of the puncta intensity and area ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain further insight into the effect of taurine on synaptic machinery, we next focused on analyzing neurites (cropped 50 μm × 20 μm section of neurites extending from pyramidal neurons; see “Materials and Methods” section for detailed description) using the SynQuant plugin in ImageJ (Wang et al, 2020 ). This method allows for the identification of puncta and the detailed quantification of the puncta intensity and area ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…It, therefore, remains unknown whether taurine affects the level of clustering of synaptic proteins at the single neuron-, neurite-, or network-levels. We took advantage of well-established methods such as SynQuant (Wang et al, 2020 ) and SynapCountJ (Mata et al, 2016 ) to analyze different synaptic parameters in entire images (networks) and primary neurites. We found that taurine not only regulated synaptic protein expression in networks but also their intensity in synaptic puncta along neurites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All statistical details of the experiments can be found in either the was quantified using the SynQuant plugin installed to Fiji software as described previously. 81 The following parameters were used to detect the puncta: 10 as a Z-score particle detection, 10 as a minimum particle size, 200 as a maximum particle size, 0.25 as a minimum fill, and 2 as a maximum width-height (WH) ratio. (4) We blindly counted the number of tau inclusion containing TauBiosensor cells.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…Second order dendrites from ten individual cells per well were imaged and analyzed. To quantify synaptic puncta, we used SynQuant 45 . To optimize the settings for SynQuant we randomly chose 10 images distributed between the different treatments.…”
Section: Imaging and Analysismentioning
confidence: 99%